The COVID-19 pandemic: an underlying factor for increased Stenotrophomonas maltophilia infections—A literature review and case study analysis - Pompilio, Arianna; Di Bonaventura, Giovanni (Frontiers in Microbiology, 2026)
Stenotrophomonas maltophilia is increasingly recognized as a major cause of healthcare-associated infections in intensive care units. It presents serious risks for immunocompromised patients and can cause severe lung infections in individuals with cystic fibrosis. Recent studies have documented a rising occurrence of S. maltophilia infections among hospitalized COVID-19 patients. However, understanding of these infections in this setting remains limited or inconsistent, with only one review specifically examining S. maltophilia infections in COVID-19 patients. This review critically evaluates all relevant studies from the literature, along with a case series, to explore the clinical significance of S. maltophilia infections in patients with COVID-19. In particular, the review discusses the prevalence, risk factors, phenotypic traits, clinical consequences, and treatment options for S. maltophilia infections in this clinical context.